Modern operating systems - Tanenbaum, Andrew S. 1944- (Pearson Education Limited, 2015)
The widely anticipated revision of this worldwide best-seller incorporates the latest developments in operating systems (OS) technologies. The fourth edition includes up-to-date materials on relevant OS. Tanenbaum also provides information on current research based on his experience as an operating systems researcher